2021
DOI: 10.1080/10872981.2021.1896160
|View full text |Cite
|
Sign up to set email alerts
|

Brief, effective experience to increase first-year medical students’ nutrition awareness

Abstract: Background: Wellness is an important concept for medical students to learn, both for their own health and for their patients. Since nutrition is an essential part of one's wellness that can positively or negatively impact one's health, it is important for medical students to learn approaches to nutritional wellness. Studies have shown that physicians' nutrition attitudes and clinical practices are positively correlated with their dietary practices. Objective: Here, we describe a brief nutrition-based education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our study showed significant decreases in intake of both calcium and vitamin D. We found a significant decrease in calcium consumption for MS1 students in 2018-19 from 804 mg to 734 mg. These findings are congruent with the Coleman et al study, which demonstrated that students were already failing to meet the daily recommended value of either micronutrient prior to the COVID-19 pandemic [ 15 ]. While the RDI of calcium is 1300 mg, the students in the Coleman study had an intake of 899 mg.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study showed significant decreases in intake of both calcium and vitamin D. We found a significant decrease in calcium consumption for MS1 students in 2018-19 from 804 mg to 734 mg. These findings are congruent with the Coleman et al study, which demonstrated that students were already failing to meet the daily recommended value of either micronutrient prior to the COVID-19 pandemic [ 15 ]. While the RDI of calcium is 1300 mg, the students in the Coleman study had an intake of 899 mg.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies such as Coleman et al have demonstrated that medical students do not meet the recommended daily food intake value of 1600-2400 calories for women, and 2000-3000 calories for men [ 14 , 15 ]. Of the 193 students who completed the Coleman survey, students on average were meeting 93.4% of the daily value.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates the need for good dietary programs and education from an early stage of medical studies irrespective of the major. As it was found in the study of Coleman et al [ 30 ], education in the first year of medical studies changed their dietary choices for the better and it may also impact the possibility to advise patients on nutrition in the future. A recent review [ 31 ] also showed that a variety of teaching approaches provided students with many benefits which are particularly important since an unhealthy diet is the cause of about 20% of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Rababah et al (2019) found that 76.9% of students reported receiving no information on nutrition awareness and most students (67.5%) expressed an interest in learning about health. The results of this study addressed the need for health literacy and health awareness in colleges and universities and highlighted the physical, psychological, psychiatric, social, and reproductive health issues that plague college students (Coleman et al, 2021). It is important for college health centers to provide healthy food education for students, which could be accomplished with the REAPS tool used in conjunction with toolkits such as MyPlate (Segal-Isaacson et al, 2022;USDA, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Nutrition education programs are designed to raise nutrition awareness with the aim of promoting healthy eating (Rababah et al, 2019). Coleman et al (2021) found that students experienced significant improvements in nutrition awareness through nutrition education in college. Improvements in eating behavior and intentions were also seen, but more promisingly, improvements led to decreases in BMI and waist circumference.…”
Section: Discussionmentioning
confidence: 99%